Post-recurrence survival of patients with non-small-cell lung cancer after curative resection with or without induction/adjuvant chemotherapy - Saisho, Shinsuke (Oxford University Press, 2013)
OBJECTIVES: Recently, the prognosis of patients with non-small-cell lung cancer (NSCLC) has improved, thanks to the standardization of adjuvant chemotherapy and the introduction of molecular-targeted drugs, notably epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors and other new anti-cancer agents. However, the survival characteristics and prognosis of patients with recurrent NSCLC after curative resection are not well understood. METHODS: Of the 430 consecutive patients with NSCLC who underwent complete surgical resection at our institution between January 2004 and July 2011, we included 76 patients with recurrence whose post-recurrence treatment and outcome could be confirmed. We then retrospectively evaluated the effect of prognostic factors on post-recurrence survival. RESULTS: There were 50 men and 26 women, and the median age at recurrence was 74.5 years. The median time from surgical resection to recurrence was 12.7 months. Thirty-eight of the 76 (50%) patients underwent multimodality treatment with surgery and preoperative and/or postoperative chemotherapy as their initial treatment. For recurrence, systemic chemotherapy was administered to 64 (84%) patients, and the disease control rate for first-line chemotherapy was 55%. The 1- and 2-year post-recurrence survival rates were 68.3 and 45.8%, respectively, and the median post-recurrence survival time was 17.7 months. Six independent prognostic factors were identified: wild-type EGFR, no adjuvant chemotherapy for the primary lung cancer, age ≥80 years at recurrence, a poor Eastern Cooperative Oncology Group performance status at recurrence, symptomatic at recurrence and no systemic chemotherapy for recurrence, which significantly decreased the post-recurrence survival. CONCLUSIONS: The prognosis of patients with NSCLC recurrence after surgery is currently improving. Our results suggested two new prognostic factors, adjuvant chemotherapy and EGFR mutations, neither of which have been previously reported. Treatment strategies for postoperative recurrence should be established based on a more detailed subdivision of factors, such as histology and molecular markers, in the future.